THE IMPLEMENTATION OF AUTHENTIC ASSESMENT IN RAISING THE STUDENT'S SPEAKING SKILL AT RELIGIUS PROGRAMS (MANPK) SENIOR HIGH SCHOOL 01 JEMBER - Hosna, Hosna; Anam, Syamsul; Maulana, Asep (Universitas Cokroaminoto Palopo, 2023)
This research was conducted with the aim of knowing the Implementation of Authentic Assessment in Improving Maharah Kalam Students of Madrasah Aliyah Religious Programs (MANPK) in MAN 01 Jember. This research used descriptive qualitative, while the data collection technique used interviews, observation, documentation, While the techniques used in this research used technical validity of the data is done by triangulation of sources and techniques. interaction analysis with the steps of data collection, data reduction, data presentation and drawing conclusions or verification. From the results of this study, there are three assessments, namely knowledge, namely the teacher uses written test instruments and oral tests. The oral test is carried out at Maharah Kalam, while the written test is carried out after one lesson or at the end of the semester. The attitude assessment carried out in the MANPK program can be seen from the discipline aspects of students both in class and in the dormitory. Assessment of skills in learning Arabic in Maharah Kalam is direct practice when the teaching and learning process in class takes place using the book Al-'Arabiyah Lil Hayah and Al-'Arabiyah Baina Yadaik.